2018
DOI: 10.11648/j.jdmp.20180404.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiabetic Activity of Aqueous Extract of Leaves from <i>Phragmanthera capitata</i> (Sprengel) S. Balle (Laurenthaceae) in <i>Wistar</i> Albino Rats

Abstract: Diabetes mellitus is a public health problem affecting about 8.4% of people in the world and knows an alarming progression in sub-Saharan Africa and in Cameroon precisely. The current therapeutic strategies have prohibitive prices, are unavailable and have harmful side-effects. So, this work aimed at contributing to the valorization of medicinal flora and `knowledge of traditional healers in Foumban, West-Cameroon, in the treatment of diabetes. An ethnopharmacological survey was conducted by consulting traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…This drop of blood was deposited on the active zone of a strip followed by automatic reading of the glycaemia 5 seconds later. The result was expressed in mg/dL of blood [4].…”
Section: Determination Of the Glycaemiamentioning
confidence: 99%
See 3 more Smart Citations
“…This drop of blood was deposited on the active zone of a strip followed by automatic reading of the glycaemia 5 seconds later. The result was expressed in mg/dL of blood [4].…”
Section: Determination Of the Glycaemiamentioning
confidence: 99%
“…Two groups made up of 3 lots of 3 rats each were constituted in addition to the three control groups (Healthy, negative and positive controls). Rats were force-fed with a 60% glucose solution at 4 g/kg body weight dose, using a gastroesophageal tube [4]. Aqueous extracts (37.5 mg/kg body weight) were used in the first group while methanol extracts (37.5 mg/kg body weight) were used in the second group.…”
Section: Preliminary Tests In Rats With Temporary Hyperglycemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous research work in our laboratory, we demonstrated that the administration of Phragmanthera capitata aqueous extract to diabetic rats significantly decreased hyperglycaemia at the dose used by the herbal medicine doctors. It showed hypolipidemic and immunomodulatory effects as well [ 12 ]. Furthermore, the water extract from P. capitata showed no toxic reactions, no change in behavior, and no mortality at a dose of 3000 mg/kg and 5000 mg/kg in mice and Wistar rats [ 7 , 13 ], while acetone, methanol, ethanol, and water extracts showed not toxic (lethal concentration > 1 mg/mL) in Brine shrimp hatchability assay.…”
Section: Introductionmentioning
confidence: 99%